Iranian Managers' Cross Cultural Negotiation Styles - Pourdadash Miri, Hossain (Universiti Sains Malaysia, 2006)
Literatures on managers' cross cultural negotiation styles have been documented particularly in Atnerica, Japan, China and Brazil. The present study intended to contribute to the Iranian managers' cross cultural negotiation styles. The purpose of the present study is to determine the impact of multicultural personality characteristic (open-mindedness, cultural empathy, emotional stability, flexibility, and social initiative), preparation before negotiation, and relationship building with foreign negotiators on three dimensions of Iranian managers' cross cultural negotiation styles (protecting honor, self-respect and dignity, and value relationship).